PREPOSISI DALAM ALBUM STAND UP AND SCREAM KARYA ASKING ALEXANDRIA - LEMPAS, BILLY B. (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2016)
ABSTRACT This study is an attempt to find out the forms and analyze the meaning of prepositions in the Album Stand Up and Scream by Asking Alexandria. The data were analyzed based on the theories of Quirk Randolph (1985) and Curme (1986). The method used in this research was descriptive method. The data of prepositions were taken from the lyrics in the Album Stand Up and Scream by Asking Alexandria. The result of this study shows that there are 5 forms of prepositions found in the 13 songs in the album based on the theory of Quirk (1985) simple preposition, compound preposition, complex preposition, marginal preposition, inflectional preposition. Based on the theory of Curme (1986), there are 13 meanings of preposition found in the Album Stand Up and Scream by Asking Alexandria. The meaning of preposition refer to place, time, purpose or target, source or origin, cause or reason, way, tool, inclusion, nature, ownership or possession, amount, size, conquest. Keywords: Prepositions, Form & Meaning, Asking Alexandria.